Analgesic efficacy of ultrasound-guided ESPB on metabolic surgery - Wang, Ying; Liu, Yan; Jie, Wen; Yang, Qiuya; Jiang, Fenglin (Frontiers in Medicine, 2025)
BackgroundThis systematic review and meta-analysis assessed the analgesic efficacy of ultrasound-guided ESPB in metabolic surgery.MethodsA systematic literature search of PubMed, the Cochrane Library, Web of Science, and Embase was conducted from database inception to February 2025 to identify randomized controlled trials (RCTs) comparing ultrasound-guided erector spinae plane block (ESPB) with either no block, sham block, or alternative regional analgesic techniques in patients undergoing metabolic surgery. Primary outcomes included 24 h postoperative opioid consumption, while secondary outcomes encompassed pain scores, time to first analgesic requirement, postoperative nausea and vomiting, and patient satisfaction. Risk of bias was assessed using the Cochrane Risk of Bias Tool, and evidence quality was evaluated using GRADE.ResultsTen RCTs involving 729 patients were included. ESPB significantly reduced 24 h opioid consumption [mean difference (MD): −6.68; 95% CI: −10.75, −2.61; p = 0.001] and resting pain scores at 24 h [MD: −0.78; 95% CI: −1.10, −0.46; p < 0.00001]. Movement pain scores were also reduced to 6, 12, 24, and 48 h (p < 0.00001 for all). ESPB prolonged the time to first rescue analgesic [MD: 14.17; 95% CI: 5.50, 22.85; p = 0.001]. However, no significant differences were observed in PONV incidence or patient satisfaction scores.ConclusionUltrasound-guided ESPB is an effective and safe analgesic technique for metabolic surgery, significantly reducing opioid consumption and pain scores while delaying the need for rescue analgesics.Systematic review registrationPROSPERO 2025 CRD420251000358. Available from https://www.crd.york.ac.uk/PROSPERO/view/CRD420251000358.